Inbreeding depression in dioecious populations of the plant Mercurialis annua: comparisons between outcrossed progeny and the progeny of self-fertilized feminized males. - Eppley, S; Pannell, J (2009)
Inbreeding depression is a key factor in the maintenance of separate sexes in plants through selection for the avoidance of self-fertilization. However, very little is known about the levels of inbreeding depression in dioecious species, obviously because it is difficult to self-fertilize males or females. We overcame this problem by clonally propagating males from lineages in a dioecious metapopulation of the European annual plant Mercurialis annua, feminizing some of them and crossing the feminized with the unfeminized clones. Using this method, we compared the fitness of selfed vs outcrossed progeny under field conditions in Spain, where this species grows naturally. Multiplicative inbreeding depression (based on seed germination, early and late survival, seed mass and pollen viability) ranged from -0.69 to 0.82, with a mean close to zero. We consider possible explanations for both the low mean and high variance in inbreeding depression in M. annua, and we discuss the implications of our results for the maintenance of dioecy over hermaphroditism.